Rancang Bangun, Penyerahan, dan Sosialisasi Sistem Informasi Penggajian - Riche, Riche; Jefri Junifer Pangaribuan; Aulia Rizky Muhammad Hendrik Noor Asegaff; Jepronel Saragih; Mirza Ilhami (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
PT XYZ is a private company engaged in the production and sale of wire materials. The employee payroll process in this company is still conducted manually using paper records, leading to inefficiencies and a high risk of errors in payroll and attendance data recording. To address this issue, a computerized payroll system was developed using the waterfall development methodology. A structured analysis and programming approach was chosen to support the system’s accuracy and consistency. In the analysis phase, a flow of document (FOD) was used to map the existing workflow, while a data flow diagram (DFD) was applied in the design phase to illustrate the data flow. This system was built using Microsoft Visual Basic.NET for the interface development, Microsoft Office Access 2007 for the database, and Crystal Report 13 for generating reports. In addition to development, training and socialization sessions were conducted for PT XYZ employees to ensure effective system use. By implementing this system, the payroll process is expected to become faster, more accurate, and transparent, thereby enhancing work efficiency and effectiveness. This development is also part of a community service partnership program that aims to contribute positively to administrative management at PT XYZ.